The correlation between modifications to corneal topography and changes in retinal vascular density and retinal thickness in myopic children after undergoing orthokeratology - Lian, Yan; Lu, Weiwei; Xu, Aiqin; Chen, Renai; Lu, Qingqing; Zhou, Weihe; Mei, Lili; Jin, Wanqing (Frontiers in Medicine, 2023)
Purpose This study aimed to investigate the relationship among changes in corneal topography, retinal vascular density, and retinal thickness in myopic children who underwent orthokeratology for 3 months. Method Thirty children with myopia wore orthokeratology lenses for 3 months. Using optical coherence tomography angiography (OCTA), the retina was imaged as 6 × 6 mm en-face images at baseline and 3 months after orthokeratology. Cornea data was acquired by topography and analyzed by customer MATLAB software. The cornea was divided into 3 zones and 9 sectors. The relative corneal refractive power shift (RCRPS) was used in this study. Changes in retinal vascular density (RVDC) and retinal thickness change (RTC) were associated with RCRPS by using spearman test. Statistical significance was set at p < 0.05. Result A significant correlation was observed between the RVDC and the RCRPS in many regions (the r was 0.375 ~ 0.548, all p value <0.05). Significant positive correlations were found between RVDC in inner and outer temple regions with RCRPS at inner and outer nasal sectors. There were no significant correlations between RTC and RCRPS in other sectors except in the central cornea and the outer nasal retina (r:0.501, p:0.006). At baseline and 3 months after wearing the orthokeratology lens, no significant differences in the retinal microvasculature or thickness (p > 0.05) were observed at any regions. Conclusion The correlation between the cornea and the retina was observed after orthokeratology. Cornea changes may affect regional retinal responses accordingly，which may explain how orthokeratology delays myopia progression partially.